1995
DOI: 10.1111/j.1151-2916.1995.tb08050.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Stearic Acid on the Injection Molding of Alumina

Abstract: This research investigated the influence of stearic acid on the injection molding of alumina, by varying the concentration of stearic acid. The interaction between stearic acid and alumina was identified using transmission infrared spectroscopy, indicating stearic acid preferentially adsorbed onto the alumina powder surface. In addition to slightly modifying the intrinsic binder viscosity, stearic acid adsorbed onto the powder surface changed the flow behavior of the mixtures from dilatant flow to pseudoplasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(33 citation statements)
references
References 12 publications
0
33
0
Order By: Relevance
“…These surface-active dispersants normally present a low melting temperature and affinity to preferentially adsorb onto powder surfaces, forming a densely thin outer layer on a particle surface which leads to a more homogeneous packing structure (Chan & Lin, 1995). However, bubbles and cracks were reported to occur as the amount of the surfactants increases, presumably owning to the reduced vaporization temperature since the surfactants are composed of mostly short molecules (Tseng & Hsu, 1999).…”
Section: Binder Formulationmentioning
confidence: 99%
“…These surface-active dispersants normally present a low melting temperature and affinity to preferentially adsorb onto powder surfaces, forming a densely thin outer layer on a particle surface which leads to a more homogeneous packing structure (Chan & Lin, 1995). However, bubbles and cracks were reported to occur as the amount of the surfactants increases, presumably owning to the reduced vaporization temperature since the surfactants are composed of mostly short molecules (Tseng & Hsu, 1999).…”
Section: Binder Formulationmentioning
confidence: 99%
“…Fatty acids are the most widely used surfactants; they are introduced to disperse suspensions of ceramic-powder and paraffin-wax in many industrial procedures. 7 Stearic acid is considered to be one of the most appropriate candidates due to its carboxylic functional-group anchoring at the powder surface and a carbon chain containing 18 carbon atoms dissolving into the binder matrix. The adsorption of the stearic acid is usually via hydrogen bonding, although covalent bonding has also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Though it is difficult for us to completely confirm the amorphous layer being of SA due to the very low melting point and extremely thin layer of SA (∼3 nm), we have proved that there is a chemical reaction (esterification) occured between the particle and SA, in which Al-O-CO band has formed induced by the treatment of ball milling based on the following FTIR analysis. 5,[13][14][15] Hence the characteristic of treated SA is quite different from pure SA including the melting temperature, for there is a strong interaction between SA and the powder. Thus, the coating seems to be SA.…”
Section: Characterizationmentioning
confidence: 99%
“…excellent homogeneity among the neighbored particles to overcome the poor compatibility between the ceramic powders and organic binders. [5][6][7][8] Tseng et al reported that the alumina feedstock rheology and the green microstructure of injection-molded ceramic-binder mixtures may be engineered by means of surface active additives. 6 Wang et al adopted SA as surface modification agent to improve the binder chemistry, which changed the ceramic powders from hydrophilicity to hydrophobicity.…”
Section: Introductionmentioning
confidence: 99%